MODEL PERILAKU STRATEGIS PENGUSAHA INDUSTRI KECIL DALAM MEMBANGUN KEUNGGULAN KOMPETITIF (STUDI KASUS PENGUSAHA BATIK TASIKMALAYA) - Widjajani ,; Dede Siti Rohimah (Media Riset Bisnis & Manajemen, 2013)
Small scale industries are characterized by "one-man-one-management", therefore a success of a small industry depends on how the owner manage his/her enterprise. Their entrepreneurial behaviour that can build competitive advantage known as strategic behaviours of the entrepreneur. This research is aimed to model strategic behaviours of the most successful Batik Enterprise's owner manager in Tasikmalaya's Batik Cluster. The research uses soft system methodology (SSM) approach to build the model. The major findings of this research indicate four kinds strategic behaviour model that related each others as a system.Keywords: Small industries, Competitive advantage, Soft system methodology